Factors Associated with Travel Time Accuracy of Dynamic Message Signs for Route Choice - Mousa Abushattal; Fadi Alhomaidat (Future Transportation)
Travel time is one of the most important pieces of information that the Dynamic Message Sign (DMS) provides to drivers. However, several variables, including traffic-related factors and DMS message characteristics, might impact the accuracy of the travel time when the DMS is used to display the travel time for alternate routes. Therefore, this study aims to look at the variables that affect the route choice’s displayed travel time accuracy as it relates to the individual driver. The accuracy of the travel time displayed on a DMS on I-75 in Saginaw, Michigan, was examined using logistic regression analysis. The results suggest that for effective traffic management for high traffic demand times (peak hour and day of the week), avoiding using travel time information displayed with other types of messages at the same time (phasing) and adapting a message update time between 2 to 3 min can improve the DMS travel time information accuracy. Practitioners and planners can use the findings to improve driver compliance with the DMS message that is being displayed.